Home service mobile application based on matching algorithm / Mohammad Naqib Norbaini - Norbaini, Mohammad Naqib (2021)
There have been major improvements in the way our job is performed in recent years, hi this, there is a place for the advancement of technology, the online platforms we work with, as well as the varied and versatile working conununity of modern businesses. Simply put, people work from everywhere and wherever today, and at any time for most entrepreneurs. We'll also find ourselves attracted to carrying jobs out of the workplace with us. Most of the business that were available in Malaysia are starting to join the on-demand businesses which means that customer can demand for the service as soon as possible. It is a great business opportunity for them to improve their sales. Therefore, a mobile application has been proposed for customer to book a service for their home and service provider can register and add their services.